Facilidades Turísticas y Desarrollo Sostenible en la parroquia Pilahuin, cantón Ambato, provincia de Tungurahua. - Pilamunga Punina, Christian Daniel (2023)
The research called "Tourism Facilities and Sustainable Development in the Pilahuin parish, Ambato canton, Tungurahua province." The main objective is to verify the relationship between the two variables, dependent and independent. In this way, in the variable Tourist Facilities (I.V.) the sample was determined, to all the authorities that work in the Centralized Autonomous Government of the Pilahuin Parish, taking dimensions such as Tourist Resources, touristic services and Touristic Infrastructure, for the other variable Sustainable Development (D.V.), it was considered a group of inhabitants who have a high school or third level degree and who know about the variable, prioritizing elements such as Environmental, Social and Economic. The methodology used in this research is Descriptive, Documentary, correlational and exploratory. Therefore, the survey was applied as an instrument to obtain true and reliable information, making items for each indicator. Based on the surveys carried out, it was stablished findings to know the problem of the investigation. Subsequently, the tabulation was carried out in Microsoft Excel and then data was transferred to a SPSS version 19 program where Cronbach's alpha was applied to measure the reliability of the surveys and with the Chi-square method, it resulted in no relationship in the general hypothesis and in the specific hypothesis 1 and 3 of Sustainable Development, but in hypothesis 2 there is a relationship. Therefore, a proposal was made to design a Tourist Signage System that contributes to sustainability in the Pilahuin parish, Ambato canton, Tungurahua province, clearly focused on tourist signage between totem poles and interpretive tables and provide entertaining information.